Heating System of Greenhouses Through Perforated Air Pipe (The Peerian Journal, 2023)
Creating an ideal microclimate ithin greenhouses is crucial for successful plant growth and maximizing crop yield. Temperature control plays a vital role in maintaining optimal conditions throughout the growing season. Perforated air pipe systems offer a innovation by distributing hot air uniformly, resulting an optimized microclimate. This article explores the benefits and functionality of using perforated air pipes to create an optimal microclimate in greenhouses.